Galvanization of Al-Si Trip-Assisted Steels - Bellhouse, Erika M. (My University, 2010)
The high strength and ductility of TRIP-assisted steels makes them ideal for automotive lightweighting. However, to be used in automotive exposed parts galvanizing is essential to provide corrosion protection. Galvanizing of TRIP steels poses two major challenges: i) the heat treatment used to obtain the TRIP steel microstructure and mechanical properties is not necessarily compatible with the higher temperatures required for hot-dip galvanizing and ii) selective oxidation of the alloying elements used in TRIP steels; Mn, Si and Al, can result in bare spot defects and unacceptable coatings. Both of these issues have been investigated.
Heat treatments compatible with continuous hot-dip galvanizing were performed on two high Al - low Si TRIP-assisted steels; one having 1.5% Al and the other having 1.0% Al and 0.5% Si. The effect of intercritical annealing (IA) temperature and isothermal bainitic transformation (IBT) time at 465 °C on the development of microstructure and mechanical properties was studied. It was determined that a sufficient quantity of stable retained austenite and an excellent combination of strength and ductility could be obtained using thermal cycles with a 465 °C IBT temperature. For the 1.5% Al steel the best combination of strength and ductility was obtained for the thermal cycle using the 50% austenite (y) IA temperature and IBT times of 90 sand 120 s. For the IBT time of 90 s the tensile strength was 895 MPa and uniform elongation was 0.26. For the IBT time of 120 s the tensile strength was 880 MPa and uniform elongation was 0.27. For the 1.0% Al - 0.5% Si steel the best combination of strength and ductility was obtained forthe 50% y IA temperature and IBT time of 120 s. This thermal cycle resulted in a tensile strength of 1009 MPa and a uniform elongation of 0.22.
The effect of process atmosphere oxygen partial pressure on oxidation and reactive wetting during galvanizing was determined for four TRIP-assisted steels having varied Si and Al contents. Three different process atmospheres were studied for each alloy: a -53 °C dew point (dp) or-50 °C dp with N2 -20% H2 , a -30 °C dp with N2 - 5% H2 and a +5 °C dp with N2 - 5% H2 . The steel chemistry and oxygen partial pressure of the process atmosphere affected oxide chemistry and morphology. For all alloys the lowest oxygen partial pressure process atmosphere resulted in the highest concentration of Si at the surface (-53 °C dp or -50 °C dp) and the -30 °C dp process atmosphere resulted in the highest concentration of Mn at the surface. The predominant oxide morphology observed at the surface of the two high Al- low Si steels comprised filmtype oxides or irregular shaped nodules whereas the two high Si steels had an oxide morphology that generally comprised spherical cap shaped nodules.
Good wetting was obtained for all alloys when using two low oxygen partial pressure process atmospheres (-53 °C dp or -50 °C dp and -30 °C dp) and poor wetting was obtained for a higher oxygen partial pressure process atmosphere ( +5 °C dp ). At the +5 °C dp a considerably larger percentage bare area in the galvanized coating was obtained for the two high Si steels when compared to the two high Al- low Si steels. For the two high Si steels poor wetting at the +5 °C dp was attributed to the oxide morphology with closely spaced Mn-Si oxide nodules being observed at the surface ofthese steels. For the 1.5% Al steel and 1.0% Al - 0.5% Si steel the poor wetting was due to thick localized MnO films at the steel surface.
Despite selective oxidation observed at the surface for the -53 °C dp or -50 °C dp and -30 °C dp process atmospheres good reactive wetting was observed. For these processing conditions a number ofreactive wetting mechanisms were identified. When oxides remained at the steel/coating interface, the oxides could be bridged by the Zn overlay, Fe2Al5Znx or Fe-Zn intermetallics. Good wetting was also attributed to aluminothermic reduction of surface oxides by the dissolved Al in the Zn bath. For some processing parameters cracking of the oxide as a result of thermal stresses in the oxide imposed during cooling from the intercritical annealing temperature to the Zn bath temperature allowed the bath metal to reach the steel substrate, thereby improving wetting. Similarly, liquid infiltration of bath metal at the oxide/steel grain boundaries also contributed to good wetting on some samples. Lastly, in some cases wetting of the oxide was observed.
Title: Galvanization of Al-Si TRIP-Assisted Steels, Author: Erika M. Bellhouse, Location: Mills